2020
DOI: 10.1111/jfpp.14647
|View full text |Cite
|
Sign up to set email alerts
|

Quality, phenolic content, antioxidant activity, and the degradation kinetic of some quality parameters in strawberry fruit coated with salicylic acid andAloe veragel

Abstract: The aim of this study was to evaluate the effect of salicylic acid (SA), Aloe vera gel (AV), and SA + AV on quality parameters of strawberry over 15 days. Weight loss, decay, and firmness increased, while ascorbic acid (AAC), total anthocyanin (TAC), total phenolic (TPC) contents, total antioxidant activity (TAA), and sensory attributes decreased significantly during the storage time in all samples. All treatments suppressed water loss, decay, and firmness and maintained higher AAC, TAA, and TPC compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 58 publications
(119 reference statements)
4
19
0
Order By: Relevance
“…As mentioned, SA can improve the activity of PAL [40,41]. This was also confirmed in a study of Salvia miltiorrhiza cell cultures, while both PAL activity and phenolic acid content were clearly improved with SA treatments [48]. In our study, hydroxycinnamic acid content generally increased in strawberry fruits treated with SA compared to the control, while the effects of MeSA and ASA were not as evident.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As mentioned, SA can improve the activity of PAL [40,41]. This was also confirmed in a study of Salvia miltiorrhiza cell cultures, while both PAL activity and phenolic acid content were clearly improved with SA treatments [48]. In our study, hydroxycinnamic acid content generally increased in strawberry fruits treated with SA compared to the control, while the effects of MeSA and ASA were not as evident.…”
Section: Discussionsupporting
confidence: 90%
“…Hydroxycinnamic acids (HCAs) are precursors for all other phenolics in the phenylpropanoid pathway and their biosynthesis is regulated by three enzymes, PAL, cinnamate 4-hydroxylase and 4-coumarate-CoA ligase [48]. As mentioned, SA can improve the activity of PAL [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PPE may also reduce the activity of cell wall degradation‐enzymes that are responsible for fruit tissue softening. Other studies have been reported similar findings for different extracts on fruit firmness such as grapefruit seed extract on grapes (Xu et al., 2007) and Aloe vera extract on strawberry and sweet cherry (Hosseinifarahi et al., 2020; Martínez‐Romero et al., 2006). Also, it has been shown that different extracts such as PPE due to their antimicrobial and antifungal compounds greatly prevent spoilage and softening of fruits (Nicosia et al., 2016).…”
Section: Resultssupporting
confidence: 53%
“…Strawberry ( Fragaria × ananassa Duch.) is one of the popular fruit worldwide with highly desirable flavor and has unique nutritive properties and high level of minerals, dietary fibers, anthocyanins, vitamins, phenolic compounds, and flavonoids (Hosseinifarahi et al, 2020; Sogvar et al, 2016). During postharvest storage, strawberry shows severe problems mainly because of fungal infection, water loss, high rate of respiration, bruising, and mechanical injuries which limit its shelf life and impose considerable financial loss to the strawberry traders.…”
Section: Introductionmentioning
confidence: 99%